Digitising English language learning for early childhood educators in Malaysian context: The rationale - Wan Jumani, Fauzi; Noor Raha, Mohd Radzuan; Ezihaslinda, Ngah; Anita, Abdul Rani; Fatimah, Ali (Pacific Early Childhood Education Research Association, 2021)
Nowadays, many kindergartens in Malaysia are striving toward using English in their daily activities with their children and some even use English language as their medium of instruction. However, some of the early childhood educators were not well equipped with the knowledge of English language. This paper aims to report the rationale for digitising English language learning through the development of Kindy Talk Application in terms of approach, content and design. Kindy Talk Application is a mobile application for Malaysian early childhood educators to utilize accurate language in their daily routine interactions and instructional language typically used at daycare centres. This development of the application stemmed from a series of workshops with 2 modules, namely Communication English and Storytelling techniques. These workshops aimed at increasing 30 Pahang early childhood educators' professional development. To ensure the sustainability of the training, the Kindy Talk Application, which uses augmented reality technology was developed to allow users to practice the daily routine and instructional language using their mobile phones in a safe autonomous learning environment. This enhances the language proficiency and confidence of Malaysian early childhood educators.